Long-term positive severe acute respiratory syndrome coronavirus 2 ribonucleic acid and therapeutic effect of antivirals in patients with coronavirus disease: Case reports - Bo Wei; Xiaofeng Hang; Ying Xie; Yuanjing Zhang; Jianrong Wang; Xinghao Cao; Jinzi J. Wu; Junxue Wang (Revista da Sociedade Brasileira de Medicina Tropical, 2020)
Abstract Coronavirus disease (COVID-19), caused by the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), has been declared a pandemic. We herein report four COVID-19 cases with long-term positive viral ribonucleic acid (RNA) for about 61 days. Despite treatment with recombinant human interferon, convalescent plasma from COVID-19 patients, arbidol, etc., nucleic acid results were still positive for SARS-CoV-2. After treatment with ritonavir-boosted danoprevir (DNVr, 100/100 mg, once daily), all four patients showed two to three consecutive negative SARS-CoV-2 RNA and were thus discharged from hospital. Therefore, DNVr may be a potentially effective antiviral for COVID-19 patients with long-term positive SARS-CoV-2 RNA.